UMP, GIP, Biotechcorp signed a memorandum of collaboration to strengthen bio-aromatic ecosystem in Malaysia - Mohd Nizam, Abdul Rashid (Penerbit UMP, 2015)

(untitled)
Universiti Malaysia Pahang (UMP), Grasse Institute of Perfumery (GIP) of France and Malaysian Biotechnology Corporation (BiotechCorp) signed a Memorandum of Collaboration (MoC) that would pave the way to forming an academic programme relating to agriculture, flavour, fragrance and colouring which would carry certification by UMP and GIP.